Effect of Additive on Asymmetric Polyvinylidene Flouride Membrane for CO2/N2 Separation - Emyra Ezzaty, Masiren (2013)
The developments of the membrane process for gas separation now get attention especially for commercial industry. The aim of this study is to determine the effect of concentration of additive in Polyvinylidene Fluoride (PVDF) dope solution and to study the performance and characteristic properties of fabrication of membrane for CO2/N2 gas separation. In this research the N-methyl-2-pyrrolidinone (NPM) is used as solvent and Lithium Nitrate (LiNO3) is used as addictive. The ratio of PVDF/NMP/H2O is 15 wt% PVDF/82 wt% NMP/3 wt% H2O for dope solution. The different quantities of additive with different concentration are added to dope solution (0.2wt%, 1.8%wt and 5wt %). For the physical and chemical characterization membrane, the Scanning Electron Microscopy (SEM) and Fourier Transform Radiation (FTIR) will be used. These researches have to calculate the gas permeability and the selectivity after single gas permeation test with different pressure. The PVDF membrane with good condition in term of selectivity, chemical stability, and thermal stability for CO2/N2 was developed. Refer to SEM analysis, the reducing of clear image for finger-like pores and sponge-like structure as 0.2wt% LiNO3 > 1.8wt% LiNO3 > 5wt% LiNO3. As the percentage of additive increase, the image of pores and structure will be less clearly. Compare to morphology image without additive, 15wt% PVDF membrane pore and structure is quite larger and longer. The additional of additive resulting the pore and structure become smaller. Membrane with additive of 5wt% LiNO3 into the dope solution could form the membrane stronger strain strength than the PVDF commercial membrane. For FTIR analysis, membranes without additive have the functional group of alkenes, alkyl halide and aromatic group. Membranes with additive have the functional group of alkenes, alkyl halide, aromatic, amine and nitro group. Gas permeation analysis, 0.2wt% LiNO3 produces a high performance for gas separation. It has a higher permeability and selectivity result. The relation of gas permeation test and SEM morphology test is the larger pore on cross section membrane will be cause the good permeability on CO2/N2 pure gas. Permeability of membrane with additive is give a high performance compared with membrane which does not have additive.